2005
DOI: 10.4049/jimmunol.175.1.147
|View full text |Cite
|
Sign up to set email alerts
|

Independent Trafficking of Ig-α/Ig-β and μ-Heavy Chain Is Facilitated by Dissociation of the B Cell Antigen Receptor Complex

Abstract: The BCR relays extracellular signals and internalizes Ag for processing and presentation. We have previously demonstrated that ligation of the BCR destabilizes Ig-α/Ig-β (Ig-αβ) from μ-H chain (μm). In this study we report that receptor destabilization represents a physical separation of μm from Ig-αβ. Sucrose gradient fractionation localized Ig-αβ to GM1-containing lipid microdomains in the absence of μm. Confocal and electron microscopy studies revealed the colocalization of unsheathed μm with clathrin-coate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 39 publications
1
25
0
Order By: Relevance
“…BCR engagement also destabilizes the sIg-Ig␣/␤ complex; physical separation of the antigen-binding and signaling components of the BCR is thought to act as a mechanism for receptor desensitization in anergic B cells (35,36), as well as to facilitate clathrin-mediated internalization of the receptor (37,38). Most sIg-dissociated Ig␣/␤ heterodimers remain on the cell surface (39,40); however, our preliminary investigation indicated that Ig␣/␤ did not remain in association with CD20.…”
Section: Discussionmentioning
confidence: 60%
“…BCR engagement also destabilizes the sIg-Ig␣/␤ complex; physical separation of the antigen-binding and signaling components of the BCR is thought to act as a mechanism for receptor desensitization in anergic B cells (35,36), as well as to facilitate clathrin-mediated internalization of the receptor (37,38). Most sIg-dissociated Ig␣/␤ heterodimers remain on the cell surface (39,40); however, our preliminary investigation indicated that Ig␣/␤ did not remain in association with CD20.…”
Section: Discussionmentioning
confidence: 60%
“…Typically, 5-l samples of complexes between nucleosomes and the different laminins (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) Analysis of proteins applied to PVDF membranes. Nucleosomes were radiolabeled with 125 I using Iodo-Beads iodination reagent (Pierce).…”
Section: Methodsmentioning
confidence: 99%
“…Samples were finally stained with uranyl acetate and lead citrate before examination by electron microscopy and evaluation as described above. In all experiments, molecules were deemed to be colocalized when 80-90% of the different sized goldconjugated antibodies met the 30 nm proximity criterion (20,21).…”
Section: Nucleosome Binding Of Aberrant Laminin ␤1 In Lupus Nephritismentioning
confidence: 99%
“…Several recent studies on the BCR have indicated that Ag cross-linking induces Ig dissociation from the Ig␣␤ heterodimer (55,56). Whereas nearly all of the surface Ig is internalized, up to 30% of the Ig␣␤ heterodimers remain on the PM and continue to signal.…”
Section: Discussionmentioning
confidence: 99%